Left atrial myxoma in a patient with a biventricular pacemaker - Przywara-Chowaniec, Brygida; Czarnecki, Łukasz; Nowalny-Kozielska, Ewa; Gawlikowski, Maciej; Opara, Mariusz; Puzio, Agata; Kawecki, Damian; Wesołowski, Bartosz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Myxomas make up about 50% of benign cardiac neoplasms. The most common location is within the left atrium. At the initial stage they do not exhibit any specific clinical symptoms, so they are often diagnosed by accident or during examinations recommended for other reasons. Here we present a case of left atrium myxoma in a patient (a man, age 68 years) with a dual chamber pacemaker. The myxoma did not reveal any clinical symptoms and was discovered in echocardiography during routine diagnostic examination preceding pacemaker implantation. The literature search made by the authors showed that this is the first recorded case of myxoma in a patient after the implantation of a biventricular pacemaker.